Tingkat Parasitasi Fopius arisanus (Hymenoptera : Braconidae) pada Lalat Buah Belimbing di Daerah Istimewa Yogyakarta - Suputa Suputa; Ahmad Taufiq Arminudin; Palupi Jatuasri; Ika Puji Rahmawati; Y. Andi Trisyono (Universitas Gadjah Mada, 2007)
Bactrocera carambolae was founf on carambola fruit in Yogyakarta Special Province and there were three species of parasitoids, i.e. Fopius arisanus, Agasnaspis sp., and Asobara sp. The population of Agasnaspis sp. and Asobara sp. were very low and was only found in Samas coastal area. F. arisanus was dominant and always found in all observation sites. There was no significant result on their parasitism (for region, F(2,35) = 0.057; p>0.005; for elevation, F(2,35)= 0.704, p>0.05; for habitat, F(2,35)= 0.215, p>0.05). Parasitism of F. arisanus on fruit fly in Yogyakarta Special Province was generally low, i.e. it ranged from 0.5495 ± 0.3843 (in Sleman), to 1.2935 ± 0.8206%. Evaluation of the existence of F. arisanus and augmentation efforts might be needed to improve its ability to parasitize fruit fly in Yogyakarta Special Province.